2008
DOI: 10.1016/j.bbadis.2008.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Activation of endoplasmic reticulum stress response following trauma-hemorrhage

Abstract: Summary Hemorrhagic trauma leads to organ dysfunction, sepsis and death. There is abnormal production of proinflammatory cytokines by Kupffer cells, tissue hypoxia and liver injury following trauma-hemorrhage. The physiological conditions consequent to trauma-hemorrhage are consistent with factors necessary to initiate endoplasmic reticulum (ER) stress and unfolded protein response. However, the contribution of ER stress to apoptosis and liver injury after trauma-hemorrhage is not known. In the present study E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 53 publications
(62 reference statements)
1
54
0
Order By: Relevance
“…These functional correlates might explain age-dependent effect of T-H on contractility and relaxation. Additionally, our experiments demonstrated enhanced endoplasmic reticulum (ER) stress in metabolically active organs following T-H (20,42). Previous studies have successfully demonstrated the usefulness of focused microarrays in profiling mitochondrial gene expression (11,43,44).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…These functional correlates might explain age-dependent effect of T-H on contractility and relaxation. Additionally, our experiments demonstrated enhanced endoplasmic reticulum (ER) stress in metabolically active organs following T-H (20,42). Previous studies have successfully demonstrated the usefulness of focused microarrays in profiling mitochondrial gene expression (11,43,44).…”
Section: Discussionmentioning
confidence: 93%
“…The upregulation of c-Myc was consistent with the observed decreased expression of genes negatively regulated by c-Myc (Cpt1 [-2.3-fold] and Gpam [-2.1-fold]). The critical function of c-Myc in regulating cardiac energy metabolism during stress and its marked upregulation after T-H in both age groups give substantial credence to its significance in energy balance in response to T-H injury and ensuing cell death (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe hemorrhage is known to cause whole body hypoxia, and reoxygenation induces oxidative injury. In the animal model of T-H, activation of endoplasmic reticulum stress, mitochondrial dysfunction and a proinflammatory response have been reported (9,29,30,(34)(35)(36)(37). Severe hemorrhage can result in systemic inflammatory response and multiple organ dysfunction leading to death (8).…”
Section: Discussionmentioning
confidence: 99%
“…Western Blot was carried out as described (30). Briefly, total proteins from tissue lysates, nuclear extracts or cytosolic fractions were resolved using 4%-12% Nupage gel (Invitrogen, Carlsbad, CA, USA) and transferred to polyvinylidene difluoride membranes.…”
Section: Western Blotmentioning
confidence: 99%